2006
DOI: 10.1177/175045890601600303
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Ethics in Practice: Issues for Perioperative Nursing

Abstract: Consent is a concept inherent in any nurse-patient relationship and provides nursing with both theoretical and practical challenges. Within the perioperative area written informed consent is obtained for surgical and anaesthetic interventions. Consent is not formally negotiated for the multitude of interventions undertaken to facilitate the most straightforward of surgical procedures. An explorative, qualitative research project was undertaken to explore the processes used by perioperative nurses for negotiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Obtaining an informed consent from an elderly patient is a complex process and the treating medical officer needs to be aware of their obligations whilst ensuring that the primary focus is good practice and concern for the patient, not a fear of litigation 3 . There should be sufficient time for full details and explanation of the procedure to be made in plain language to the patient, along with details about alternative treatments, risks and benefits 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining an informed consent from an elderly patient is a complex process and the treating medical officer needs to be aware of their obligations whilst ensuring that the primary focus is good practice and concern for the patient, not a fear of litigation 3 . There should be sufficient time for full details and explanation of the procedure to be made in plain language to the patient, along with details about alternative treatments, risks and benefits 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The basic principles of informed consent have been well established over time and are underpinned by the acceptance that every adult with legal capacity has a right to decide what shall be done with their own body. Any health care provider who performs a procedure without the patient's consent commits assault and is liable for damages which can be claimed against them 3 . In obtaining an informed consent from a patient, the medical officer must disclose details of the proposed treatment, any alternative treatments available and the risks and benefits of all treatment options, thus allowing the patient to consider all the information given and make an informed decision 1 .…”
Section: The Role Of the Perioperative Nurse In Patient Advocacymentioning
confidence: 99%
“…The first and second author individually analysed the data by reading the field notes several times to become familiar with the text. By interrogating the data (Richardson‐Tench et al, 2018), themes and/or patterns within the midwives reflections were able to be identified. Emergent qualitative themes were cross‐referenced between the first and second authors until consensus was reached.…”
Section: Methodsmentioning
confidence: 99%
“…A qualitative approach was used to enable a deeper exploration (Richardson-Tench et al, 2018), and an understanding of what mattered, what was valued and why (Hammond, 2013) to the participants who attended one of the full-day workshops undertaken in Queensland: two in Brisbane, one in Townsville and one in Cairns.…”
Section: Participant Recruitmentmentioning
confidence: 99%
“…It continually advances clinical practice standards and ensures that these standards are effective and evidence-based (Slade et al, 2018). Research has long been an important part of health and allied health (Richardson-Tench et al, 2018). In social work, there is no single understanding of what constitutes social work research.…”
Section: Purposementioning
confidence: 99%